Biologically Inspired Execution Framework for Vulnerable Workflow Systems - Safdar, S.; Hassan, M.F.; Qureshi, M.A; Akhbar, R. (LJS Publisher and IJCSIS Press, 2009)
The main objective of the research is to introduce a biologically inspired execution framework for workflow systems under threat due to some intrusion attack. Usually vulnerable systems need to be stop and put into wait state, hence to insure the data security and privacy while being recovered. This research ensures the availability of services and data to the end user by keeping the data security, privacy and integrity intact. To achieve the specified goals, the behavior of chameleons and concept of hibernation has been considered in combination. Hence the workflow systems become more robust using biologically inspired methods and remain available to the business consumers safely even in a vulnerable state.